Simplify the expression. (4 – 1)[(1 + 6) + 2] 23 27 42 45

Question

Simplify the expression.

(4 – 1)[(1 + 6) + 2]

23

27

42

45

in progress 0
Delilah 2 weeks 2021-10-10T23:17:57+00:00 1 Answer 0

Answers ( )

    0
    2021-10-10T23:19:35+00:00

    Always simplify expressions in the order of PMDAS
    (Parenthesis, Multiplication, Division, Addition, Subtraction)
    (4-1) = (3)
    [(1+6) + 2] = [7 + 2] = (9)
    (3)x(9) = 27
    The answer is 27

Leave an answer

Browse
Browse

27:3+15-4x7+3-1=? ( )